Multilayered Electrospun/Electrosprayed Polyvinylidene Fluoride+Zinc Oxide Nanofiber Mats with Enhanced Piezoelectricity - Sheyda Mirjalali; Roohollah Bagherzadeh; Shayan Abrishami; Mohsen Asadnia; Shujuan Huang; Aron Michael; Shuhua Peng; Chun‐Hui Wang; Shuying Wu (Macromolecular Materials and Engineering, 2023)
Abstract Electrospun polyvinylidene fluoride (PVDF) nanofibers have been widely used in the fabrication of flexible piezoelectric sensors and nanogenerators, due to their excellent mechanical properties. However, their relatively low piezoelectricity is still a critical issue. Herein, a new and effective route to enhance the piezoelectricity of PVDF nanofiber mats by electrospraying zinc oxide (ZnO) nanoparticles between layers of PVDF nanofibers is demonstrated. As compared to the conventional way of dispersing ZnO nanoparticles into PVDF solution for electrospinning nanofiber mats, this approach results in multilayered PVDF+ZnO nanofiber mats with significantly increased piezoelectricity. For example, 6.2 times higher output is achieved when 100% of ZnO (relative to PVDF quantity) is electrosprayed between PVDF nanofibers. Moreover, this new method enables higher loading of ZnO without having processing challenges and the maximum peak voltage of ≈3 V is achieved, when ZnO content increases up to 150%. Additionally, it is shown that the samples with equal amount of material but consisting of different number of layers have no significant difference. This work demonstrates that the proposed multilayer design provides an alternative strategy to enhance the piezoelectricity of PVDF nanofibers, which can be readily scaled up for mass production.